FAKE NEWS AND ITS IMPLICATIONS FOR THE ACHIEVEMENT OF SUSTAINABLE DEVELOPMENT GOALS IN DELTA STATE - Hannah Emuobosa ivwighren; Valeria Oghenetejiri Mukoro (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2026)
This paper has discussed the implications of fake news on the realization of Sustainable Development Goals (SDGs) in Delta State, Nigeria. The issue of fake news has progressively interfered with health communication, education programs, and peace-building efforts, as well as trust in institutions- all of which are at the core of SDGs 3, 4, and 16. A mixed methods design was adopted, and 385 valid responses out of 400 questionnaires issued were collected as quantitative data, and 18 key informant interviews with government officials, media professionals, civil society actors, and community leaders were conducted as qualitative data. The quantitative analysis with descriptive statistics, correlation, and regression found that there was a significant negative association between exposure to fake news and awareness of SDG-related initiatives and also demonstrated that exposure to fake news is a significant predictor of low engagement in development programs. Thematic analysis of the interview data proved that fake news dissemination is primarily supported by social media, political actors, blogs, and oral community networks, which erode the trust of people and disturb health, education, and peacebuilding. The research concludes that fake news is a serious challenge to sustainable development in Delta State. It proposes the intensification of media literacy, the improvement of open communication, the institutionalization of fact-checking systems, and community-based sensitization to reduce the effects of misinformation and lead to the achievement of SDGs.